2022
DOI: 10.1002/pip.3571
|View full text |Cite
|
Sign up to set email alerts
|

Determination of dominant recombination site in perovskite solar cells through illumination‐side‐dependent impedance spectroscopy

Abstract: Perovskite solar cells (PSCs) have attracted wide attention due to their capacity to achieve high‐power conversion efficiencies. However, the high trap‐assisted recombination taking place in the active layer leads to performance loss in PSCs. In particular, the excessive recombination at the interface between the perovskite active layer and the carrier selective contacts can be especially problematic. Therefore, the identification of the dominant recombination pathways in a given PSC architecture is of signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…An R eh value close to or equal to 1 indicated that either the bulk recombination is dominant or that both perovskite interfaces have the same recombination rate. The more the R eh value increases above 1, the more the HTM interface recombination would dominate, and the more it decreases below 1, the more the ETM interface recombination would dominate . It can be seen from Figure that under OC conditions there is a significant difference between the Nyquist plots of the device measured under illumination from each side.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…An R eh value close to or equal to 1 indicated that either the bulk recombination is dominant or that both perovskite interfaces have the same recombination rate. The more the R eh value increases above 1, the more the HTM interface recombination would dominate, and the more it decreases below 1, the more the ETM interface recombination would dominate . It can be seen from Figure that under OC conditions there is a significant difference between the Nyquist plots of the device measured under illumination from each side.…”
Section: Resultsmentioning
confidence: 90%
“…The more the R eh value increases above 1, the more the HTM interface recombination would dominate, and the more it decreases below 1, the more the ETM interface recombination would dominate. 18 It can be seen from Figure 3 that under OC conditions there is a significant difference between the Nyquist plots of the device measured under illumination from each side. It is seen that when the device is illuminated from the c-TiO 2 side, a higher rate of recombination in the device is present, as suggested by the smaller semicircle and the smaller recombination resistance value R (see Table S1).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the J sc values from both the FTO and ITO sides show a linear relationship (Fig. S4b and S5b) with the simulated light intensity, indicating the charge carriers recombination caused by defects is low in the device [32][33][34][35][36] .…”
Section: Single-side Illuminationmentioning
confidence: 99%
“…To examine the photophysics of such a dual-irradiation PSC system, the time of ight (TOF) photoconductivity, small perturbation transient photovoltaic (TPV), nite-difference time-domain (FDTD) optical simulations were performed, collectively revealing that fast interfacial charge extraction and transportation occurring at the two quasi p-n interfaces are responsible for this PCE enhancement. Furthermore, the illumination-side-dependent impedance spectroscopy (ISD-IS) 32 was used to infer the dominant recombination pathway (e.g., interface or bulk) and validate the presence of two quasi-interfacial p-n junctions in the PSC. Our new PSC structure with a dual-irradiation con guration offers a new insight into perovskite photovoltaic physics and device integration, and this type of novel PSC dual-irradiation systems is potentially useful for many applications.…”
mentioning
confidence: 99%